Efficient removal of water bacteria and viruses using electrospun nanofibers (2020)
Pathogenic contamination has been considered as a significant worldwide water quality concern. Due to providing promising opportunities for the production of nanocomposite membranes with tailored porosity, adjustable pore size, and scaled-up ability of biomolecules incorporation, electrospinning has become the center of attention. This review intends to provide a detailed summary of the recent advances in the fabrication of antibacterial and antiviral electrospun nanofibers and discuss their application efficiency as a water filtration membrane. The current review attempts to give a functionalist perspective of the fundamental progress in construction strategies of antibacterial and antiviral electrospun nanofibers. The review provides a list of antibacterial and antiviral agents commonly used as water membrane filters and discusses the challenges in the incorporation process. We have thoroughly studied the recent application of functionalized electrospun nanofibers in the water disinfection process, with an emphasis on their efficiency. Moreover, different antibacterial and antiviral assay techniques for membranes are discussed, the gaps and limitations are highlighted and promising strategies to overcome barriers are studies.